Pencegahan kecurangan ANALISIS PENGARUH PENGENDALIAN INTERNAL,SISTEM INFORMASI AKUNTANSI DAN MORALITAS MANAJEMEN TERHADAP PENCEGAHAN KECURANGAN (FRAUD) DALAM PENGELOLAAN PERSEDIAAN (Studi Kasus Pada PT Rukun Semangat Abadi): Pengaruh pengendalian internal, sistem informasi akuntansi, dan moralitas manajemen terhadap pencegahan kecurangan - Devita Dwi Nur Insani; Erna Puspita; Mar'atus Solikah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
The increasingly rapid development of the business world requires good company management. Apart from that, companies definitely face several obstacles, one of which is fraud. One of the obstacles at PT Rukun Semangat Abadi is related to inventory. This can cause losses for the company, so maximum supervision is needed. The formulation of the research problem is whether internal control, accounting information systems, and management morality partially and simultaneously influence the prevention of fraud in inventory management (Case Study at PT Rukun Semangat Abadi). The aim of this research is to analyze the influence of internal control, accounting information systems, and management morality partially and simultaneously on preventing fraud in inventory management (Case Study at PT Rukun Semangat Abadi). This research uses causality research type. This type of research is quantitative research. This research used a questionnaire as a data collection tool with a total of 72 respondents from accounting, purchasing, ppic, production and warehouse departments. The results of the research show that internal control, accounting information systems, and management morality have a partially significant influence on fraud prevention in inventory management and the results of the F test research on internal control, accounting information systems, and management morality have a simultaneous significant influence on fraud prevention. (fraud) in inventory management at PT Rukun Semangat Abadi.